Counseling Guidance Service Model in Preventing Radicalism Among Students of the Faculty of Da'wah and Communication at UIN North Sumatra - Nasution, Syawaluddin; Zainun, Zainun (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to examine an effective guidance and counseling service model in preventing the spread of radicalism among students of the Faculty of Da'wah and Communication of UIN North Sumatra. This research focuses on identifying the potential emergence of radicalism characterized by dissatisfaction with government policies, which is often expressed through demonstrations. The method used is a qualitative approach with interviews and observations of students and lecturers at the faculty. The results showed that structured guidance and counseling interventions, including orientation services, individual counseling, group counseling, and multicultural counseling, were able to increase students' awareness of the negative impact of radicalization. In addition, the role of faculty leaders in supervising and enforcing sanctions against potentially extreme activities is also very important. This article concludes that the implementation of a comprehensive guidance and counseling service model is not only effective in preventing radicalization, but also contributes to the formation of a more tolerant and inclusive student character. Recommendations are given for further development in the implementation of guidance programs that can reach all students.